(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
The article presents the main stages of make up mathematical problems. Three foundations of making problems are described: the form, the contents and the solution of the problem. The analyzed material gives evidence that pupils’ making up mathematical problems is a tool for developing universal practical operations in maths class.